A new species of Agathoxylon Hartig from the Sriperumbudur formation, Tamil Nadu, India - D, Kumarasamy (Journal of Research in Biology, 2014)
Sriperumbudur Formation is one of the Upper Gondwana rock Formations found along the Palar basin, Tamil Nadu, India. The rock units found in this Formation are arenaceous and argillaceous, consists of green shales, clays and sandstones with limestone intercalations. These shales contain animal and plant remains of Upper Jurassic-Lower Cretaceous age. The present work is about a piece of petrified secondary wood of conifer having affinity with Araucariaceae. Based on the anatomical characters the present wood is identified as a new species of Agathoxylon Hartig.